Single-cell laser emitting cytometry for label-free nucleolus fingerprinting - Fang, Guocheng (2024)
The nucleolus, a recognized biomolecular condensate, serves as the hub for ribosome biogenesis within the cell nucleus. Its quantity and morphology are discernible indicators of cellular functional states. However, precise identification and quantification of nucleoli remain challenging without specific labeling, particularly for suspended cells, tissue-level analysis and high-throughput applications. Here we introduce a single-cell laser emitting cytometry (SLEC) for label-free nucleolus differentiation through light-matter interactions within a Fabry-Perot resonator. The separated gain medium enhances the threshold difference by 36-fold between nucleolus and its surroundings, enabling selective laser emissions at nucleolar area while maintaining lower-order mode. The laser emission image provides insights into structural inhomogeneity, temporal fluid-like dynamics, and pathological application. Lasing spectral fingerprint depicts the quantity and size of nucleoli within a single cell, showcasing the label-free flow cytometry for nucleolus. This approach holds promise for nucleolus-guided cell screening and drug evaluation, advancing the study of diseases such as cancer and neurodegenerative disorders.